2018
DOI: 10.1556/0806.46.2018.036
|View full text |Cite
|
Sign up to set email alerts
|

Grain filling variation in winter wheat, barley and triticale in pannonian environments

Abstract: Knowledge about the comparative development and grain filling of winter cereals under different environmental conditions is important for stable and high yielding crop production. The objective of this work was to compare patterns of grain filling in bread wheat, barley and triticale grown in the Pannonian region, as well as to investigate relationships among grain filling parameters, time to anthesis and grain yield. The trials with 12 winter cereal genotypes were carried out in four successive seasons at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
1
2
1
Order By: Relevance
“…An earlier anthesis date shifted the grain filling period towards better environmental conditions, resulting in a GW increase in the modern barley cultivars (data not shown). These findings contradict those previously reported (Serrago et al 2013, Mirosavljević et al 2018a, which suggested that the photosynthesis assimilation rate is more important than grain filling duration.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…An earlier anthesis date shifted the grain filling period towards better environmental conditions, resulting in a GW increase in the modern barley cultivars (data not shown). These findings contradict those previously reported (Serrago et al 2013, Mirosavljević et al 2018a, which suggested that the photosynthesis assimilation rate is more important than grain filling duration.…”
Section: Discussioncontrasting
confidence: 99%
“…Although grain yield is formed continually during the entire period from sowing to maturity, certain developmental stages are more decisive than others in determining the final grain yield (Slafer 2003). For example, in different cereal crops, stem elongation has been recognized as a crucial phase for the determination of grain number per spike and unit area (GN) (González et al 2011), while the periods from booting to anthesis (Ugarte et al 2007) and grain filling period (Mirosavljević et al 2018a) are essential for grain growth and final weight. In addition, anthesis date has also been identified as an important trait for the adjustment of the crop phenology to the available resources and for cultivar adaptation to specific environmental conditions (Reynolds et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Wheat genotypes reacted differently in the two growing seasons, giving high results in most of the traits that contribute directly to grain yield during crop years (Ristić et al, 2009;Popovic et al 2020c;Mandić et al, 2020;Đurić et al, 2020;Mirosavljevic et al, 2018;. Similar results were obtained in the research of Milanovic et al (2019;; Popovic et al, (2020c) and Rakascan et al (2019a;2019b;2021).…”
Section: Correlations Between Tested Parameterssupporting
confidence: 57%
“…(2021) also showed that an increase in the grain-filling rate in the late period and a reduction in its fluctuation were key to increasing kernel weight, and the wheat grain-filling process is dominated by the regional ecological environment, especially temperature and light. Grain-filling characteristics vary depending on environmental conditions ( Mirosavljević et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%